Brain perivascular spaces and autism: clinical and pathogenic implications from an innovative volumetric MRI study - Sotgiu, Maria Alessandra; Lo Jacono, Alessandro; Barisano, Giuseppe; Saderi, Laura; Cavassa, Vanna; Montella, Andrea; Crivelli, Paola; Carta, Alessandra; Sotgiu, Stefano (Frontiers in Neuroscience, 2023)
Our single-center case-control study aimed to evaluate the unclear glymphatic system alteration in autism spectrum disorder (ASD) through an innovative neuroimaging tool which allows to segment and quantify perivascular spaces in the white matter (WM-PVS) with filtering of non-structured noise and increase of the contrast-ratio between perivascular spaces and the surrounding parenchyma. Briefly, files of 65 ASD and 71 control patients were studied. We considered: ASD type, diagnosis and severity level and comorbidities (i.e., intellectual disability, attention-deficit hyperactivity disorder, epilepsy, sleep disturbances). We also examined diagnoses other than ASD and their associated comorbidities in the control group. We found that WM-PVS volume is significantly associated with male sex: males had higher WM-PVS volume compared to females (p=0.01). WM-PVS dilation is also directly associated with ASD severity and younger age (< 4 years). In ASD patients, higher WM-PVS volume was related with insomnia whereas no relation was found with epilepsy or IQ. We concluded that WM-PVS dilation can be a neuroimaging feature of male ASD patients, particularly the youngest and most severe ones, which may rely on male-specific risk factors acting early during neurodevelopment, such as a transient excess of extra-axial CSF volume. Our findings can corroborate the well-known strong male epidemiological preponderance of autism worldwide.